Geographic variation in natal dispersal of Northern Spotted Owls over 28 years. (13th June 2018) - Hollenbeck, Jeff P.; Haig, Susan M.; Forsman, Eric D.; Wiens, J. David
Abstract: The most recent comprehensive estimates of Northern Spotted Owl ( Strix occidentalis caurina ) natal dispersal distances were reported in 2002. Since then, Northern Spotted Owl populations have experienced substantial demographic changes, with potential attendant changes in natal dispersal distances, including temporal or geographic trends. We analyzed the natal dispersal of Northern Spotted Owls during 1985–2012 in Oregon and Washington, USA ( n = 1, 534 dispersal events), to determine current natal dispersal distances and to evaluate potential trends that may inform management actions. Mean net dispersal distance (natal site to site of first attempted breeding) was 23.8 km ± 19.2 km SD, with females dispersing ∼50% farther than males. Net dispersal distance varied by ecoregion (Washington Coast and Cascades, Washington Eastern Cascades, Oregon Coast Range, Oregon and California Cascades, and Oregon and California Klamath) but declined similarly in all ecoregions over time (∼1 km yr −1 ). Dispersal direction also varied by ecoregion, following coarse-scale forest habitat configuration, and was bimodal (north–south) in the Oregon Coast Range, south–southwest in the Oregon and California Cascades, and showed little directionality in the Washington Eastern Cascades, Washington Coast and Cascades, and Oregon and California Klamath. Long-distance dispersal events (>50 km) also varied by ecoregion (mean: 62.3–99.5 km), with most long-distance dispersal (8% of dispersers; distances up to 177 km) originating in southern ecoregions. We found no direct relationship between Barred Owl ( Strix varia ) detections near natal or settling locations and dispersal distance. These findings, particularly the declining trend of dispersal distances, may inform management actions aimed toward conservation of the Northern Spotted Owl.